Antioxidant and Antiinflammatory Activities of Different Solvent Extracts and Isolated Compounds of Ipomoea pes-caprae (L) Sweet of Sunderban Mangrove Eco-complex - Banerjee, D.; Hazra, A.K.; Seal, T.; Sur, T.; Bhattacharya, D.; Ray, J.; Mukherjee, A.; Mukherjee, B. (Asian Journal of Chemistry, 2013)
In the present study, we carried out for the first time the antioxidant and antiinflammmatory activities of the different solvent extracts of the plant Ipomoea pes-caprae (L) sweet grown up in the marine enviornment of the Sunderban Mangrove eco-complex. It was observed that chloroform and ethyl acetate solvent extracts obtained from the methanolic extract of the plant had significant antioxidant and antiinflammatory activities. To trace the molecules responsible for these bioactivities, the chemical investigation of the plant yielded four pure compounds, 7-hydroxy-6-methoxycoumarin; 5,7,4'-trimethoxykaempferol; 3,7,8,3'4'-pentahydroxy flavone; trans-[3-(4'-hydroxyphenyl)-2-propenoic acid] which were identified by spectral methods. These compounds when tested individually, showed appreciable radical scavenging activities.